FABP and Some Related Diabetic Parameters Among Adolescents with Toxoplasma gondii - Riyadh Shakir Al-Halbousi , Yousif; Al-Warid, Harith Saeed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Recently, it has been revealed that Toxoplasmosis may be associated with some factors related to type 2 diabetes, such as glucose, insulin, the Homeostatic Model Assessment for Insulin Resistant (HOMA-IR), and Fatty acid binding protein (FABP). Therefore, the current study aimed to specify how Toxoplasma gondii (T.gondii) infection affects glucose, insulin, HOMA-IR, and FABP among adolescents. From October to December 2022, this study was carried out at Al Madain Hospital in Baghdad. For a group of adolescents visiting the hospital, an ELISA test was performed to check their anti-T.gondii antibodies. Ninety adolescents were selected to participate in the study on the basis of this examination. They were divided into two groups: those who tested positive for the parasite (n = 45) and those who tested negative (n = 45), the control group. Measurements were performed on each participant's adolescence: weight for age percentile, weight for age z score, glucose, insulin, HOMA-IR, and FABP. Results showed that the T. gondii positive group had a significantly (P˂0.05) higher weight for age percentile (86.84±2.66) and z score (1.29 ±0.11) versus the control group. Results also showed that those overweight adolescents with seropositive antibodies had significantly (P˂0.05) greater levels of each glucose, insulin, HOMA-IR , and FABP than did a seronegative group of adolescents